Indoor Air Pollution as a Risk Factor of Acute Lower Respiratory Tract Infection in Children - Acharya, Niraj; Mishra, Pradip; Gupta, Veena (Journal of Nepalgunj Medical College, 2017)
Introduction: This study was conducted to find out if indoor air pollution has any risk in occurrence of acute lower respiratory tract infection (ALRI) in children. Materials and methods: It was a case control study conducted on total 214 children 107 cases and 107 controls fulfilling the inclusion criteria with age and sex matched. Detailed history and physical examination was done after taking informed consent. History of upper respiratory tract infection in the family members and siblings, history of smoking by various family members, details of cooking fuel and indoor pollution was also recorded. Results: Those families using wood as a cooking material were associated with higher risk of ALRI (p=0.0001). Exposure to domestic animal was significantly positively associated (p=0.0001) and seven times higher risk to develop ALRI as compared to control group. Those children of case group who did not have separate kitchen were having nine times higher risk of ALRI (p=0.001). Family history of smoking was associated with six times increased risk of ALRI (p=0.001). With the use of kerosene lamps risk of ALRI was increased by 1.44 times (p=0.012). Conclusions: The significant environmental risk factors for ALRI were wood as cooking material, presence of domestic animal, place for cooking, family history of smoking, absence of windows and kerosene lamp as a source of light. Journal of Nepalgunj Medical College Vol.13(1) 2015: 5-7